PEMODELAN STOKASTIK CURAH HUJAN DARI BEBERAPA STASIUN CURAH HUJAN WILAYAH TANGGAMUS - Ahmad Zakaria; Geleng Perangin Angin; Qodri Ismail (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2014)
This research is to study the periodic and stochastic models in the series of daily rainfall data. The study was conducted using daily rainfall data with a data length of 25 years (1977-2001) from the station of Banjar Agung, Gisting and Gunung Batu. This research used secondary rainfall data from Tanggamus, This study change the series of daily rainfall data into the sepektrum rainfall using FFT (Fast Fourier Transform). Periodicity of daily rainfall data were presented by using 512 rainfall. Stochastic series of rainfall data are assumed as the difference (error) between the rainfall data with periodic rainfall model. Results of this study is the correlation coefficient from three rainfall stations In this study, the correlation coefficient (R) between the data and the periodic model is 0,9974, between stochastic data series and stochastic models is 0,9996, and between data and periodic stochastic models is 0,99997. From these results it can be concluded that the periodic stochastic models of rainfall from Tanggamus periodic models using 512 rainfall data, the approach provides a very significant.